Design and fabrication of optical straight channel waveguide / Hasnormiza Hassan - Hassan, Hasnormiza (2006)
This paper reports the fabrication of optical straight channel waveguide using coating process. The first part will be fabricating a planar waveguide by coating thin film of polymer SU-8. The refractive index for SU-8 is 1.58. From here, a channel waveguide (straight and taper) was successfully designed using FIMMPROP software. And the widths for straight channel investigated are between 1.4 µm and 10 µm. For the taper waveguide, the input width was design at 10.0 um and output width 1.4 um. An initial design with 65.7% efficiency was optimised using a commercial optimizer. The final optimum design gives a power transfer efficiency of 86%. But the pattern cannot be written on the sample because of technical problem in the operation of the equipment. At the end of this project, a planar polymer waveguide was fabricated and a single mode straight waveguide and an optimised taper with 86% power transfer efficiency were designed. This project should be continued for the next time. This process is easy and simply for any design of polymer waveguide.